Determining the buried concrete amount using GPR/GPS combination method - Ucar, Celalettin; Sanli, Fusun Balik (SELCUK UNIV PRESS, 2022)
This paper investigates the possibility of describing location based NDT (Non-Destructive Testing) samples for an officially finalized project of a buried concrete layer beneath the Istanbul-Millet Street, by the combination of high frequency GPR and CORS-GPS. For this purpose, field works and laboratory studies were performed. First, data acquisition was carried out over the asphalt surface along the construction route of the street. Reflected/scattered electromagnetic wave fields was studied over the processed radargram of the concrete layer. Hence, the upper and lower boundaries of buried concrete layer were determined as a value of depth and coordinate based on spatial dataset, where there was no information about the current amount of constructed concrete. According to the measurement results, the marked location of reflected/scattered wave field on the processed radargrams defined the newly constructed concrete layer. The vertical distance between upper and lower boundaries of the layer defines the thickness of concrete layer. All types of buried layers such as C-25 road concrete, plaster or asphalt have been extracted from the entire data using the amplitude differences.
Keywords: Concrete; GPR; NDT; EM Wave Field; GPS; GROUND-PENETRATING RADAR; FORENSIC ARCHAEOLOGY; GPR DATA; SOIL; Engineering